Diisodecyl phthalate aggravates thyroid autoimmune injury in thyroglobulin-sensitized rats via endoplasmic reticulum stress-mediated apoptosis and Th17/Treg dysregulation - Zixin Tian; Jianwei Gao; Zhenjie Lu; Keyi Chen; Wanjia Lv; Mei Ye; Yajun Wang; Yanling Sun; Xu Yang; Ping Ma; Yang Wu (Food and Chemical Toxicology, 2026)

Assessing the equity and efficiency of crop and livestock-related agricultural greenhouse gas emissions contributes to achieving regionally differentiated emission mitigation - Xin Chen; Yuping Bai; Yecui Hu; Xin Xuan; Gaurav Sikka; Keyi Lyu; Guofeng Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

The acid polysaccharides extracted from Moringa leaf improve DSS-induced ulcerative colitis by targeting intestinal microbiota metabolism - Wen Lang; Xinyun Qin; Yizhe Dou; Keyi Nong; Ruixue Cao; Tingyu Chen; Wanyan Chen; Bin Zhang; Zheng Yang; Bowen Tian; Jijun Wang; Lianbin Li; et al. (Food Research International, 2026)

Hydrogen production via self-heated methanol steam reforming driven by low temperature catalytic hydrogen combustion in a microreactor - Yuehao Li; Xinlong Zhao; Keyi Feng; Yinfeng Wang; Huicong Yao; Lei Wang; Xiaotao Bi; Yuezhao Zhu (Chemical Engineering Journal, 2026)

Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

Comparative plastid genomics of five Ormosia species (fabaceae): insights into structural variation and morphological homoplasy - Shihong Zhang; Fengcheng Deng; Yixiong Zhao; Jiating Wang; Dipak Khadka; Jieyu Lin; Yuhua Hu; Keyi Fu; Lei Jiang; Mingxuan Zheng; Shi Shi (Plant Systematics and Evolution, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

Data-Driven Coastal Nutrients Estimation: Current Status, Research Gaps, and Future Developments - Sihan Ni; Jin Qi; Xiangbin Ran; Zhiqiang Liu; Sensen Wu; Minyu Wang; Keyi Yang; Chengfeng Le; Zhenhong Du (Water Research, 2026)

ΔA146Ply exerts anti-triple-negative breast cancer effects by inducing ferroptosis via regulation of the CYP24A1-mediated calcitriol-vitamin D receptor pathway - Ye Yu; Zhengkun Zhang; Dingxue Wang; Xin Bai; Dan He; Xuxu Ji; Zhaoru Yin; Keyi Xu; Ji Liu; Jiaqiong Zou (Toxicology and Applied Pharmacology, 2026)

Distance-aware cooperative Kriging-assisted evolutionary algorithm for expensive many-objective optimization - Junhua Liu; Keyi Kou; Wei Zhang; Meng Wang; Mengnan Tian (Swarm and Evolutionary Computation, 2026)

Seasonal eco-hydrological dynamics of China’s Dongting and Poyang Lake wetlands: A 26-year meta-analysis - Shafeeq Ur Rahman; Jing-Cheng Han; Ghulam Yasin; Keyi Wang; Yulei Xie; Yuefei Huang (Process Safety and Environmental Protection, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

A transcriptome dataset for early phenotypic sex differentiation in the mud crab Scylla paramamosain - Haolin Yang; Zhiqiang Liu; Chunyan Ma; Wei Wang; Lingbo Ma; Keyi Ma (Frontiers in Marine Science, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Measurement and prediction of water-energy-food-economy-ecology coupling coordination degree in Shandong Province, China - Chenjun Zhang; Man Li; Xiangyang Zhao; Yuze Wang; Keyi Ju (Ecological Modelling, 2026)

One-step treatment of refractory organic pollutants from landfill leachate: alternating magnetic field synergies persulfate activation and in-situ coagulation - Dawei Wang; Yingying Li; Yilan Jiang; Yihan Zhu; Na Huang; Keyi Gao; Jiarong Li; Shijie You (Chemical Engineering Journal, 2026)

Impact of emission inventory uncertainty on secondary inorganic aerosol simulation over Beijing–Tianjin–Hebei region - Yulong Li; Xiao Tang; Keyi Chen; Lei Kong; Wei Feng; Tianming Lu; Kai Cao; Quan Zhang; Zifa Wang (Atmospheric Pollution Research, 2026)

Comparative transcriptomic analysis of the megalopa metamorphosis development reveals candidate genes associated with developmental remodeling and putative brachyurization in the mud crab Scylla paramamosain - Keyi Ma; Likun Xu; Zhiqiang Liu; Xueyang Wang; Lingbo Ma; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2026)

Post-transcriptional regulation of ABCB1 by miR-34-5p is associated with emamectin benzoate susceptibility in Spodoptera frugiperda - Congsai Wang; Jingdong Li; Zikun Wang; Liying Wu; Huiling Huang; Yunkun Zi; Binrui Bai; Keyi Chen; Hongsong Chen; Huihua Tan; Yutao Xiao; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Root hair-mediated rhizosphere assembly acts as a resilience trait against microplastic-induced dissemination of antibiotic resistance - Zhihui Jin; Guangjun Wang; Yifei Wang; Qing Zhu; Ping Gong; Keyi Chen; Ming Yuan; Huaiying Yao (Journal of Environmental Sciences, 2026)

Self-assembled and reversibly esterified hierarchical networks enable tough, anti-swelling and recyclable nanocomposite hydrogel - Zhengxu Jin; Ying Chen; Feihong Hu; Huizhu Wang; Qianyue Zeng; Keyi Yang; Hong Chen; Xiaoming Huang; Jing Xie; Jianshu Li (Chemical Engineering Journal, 2026)

Pyrolysis-derived recovered glass fiber-engineered ultrafiltration membrane for dyeing wastewater treatment - Fengzhi Guo; Haolun Wang; Fan Shao; Jinzhi Jiang; Guorui Li; Xinmeng Ma; Haoran Ma; Keyi Li; Lu Gong; Yue Ma; Changtao Yue (Chemical Engineering Journal, 2026)

Corrigendum to ‘Constitutive overexpression of ATP-binding cassette transporters contributes to emamectin benzoate resistance in Spodoptera frugiperda’ [Pesticide Biochemistry and Physiology, 219 (2026) 106980] - Congsai Wang; Zikun Wang; Jingdong Li; Yunkun Zi; Huiling Huang; Binrui Bai; Keyi Chen; Jing Wang; Hongsong Chen; Huihua Tan; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Vertical distribution pattern, preferred life strategies and environmental response of prokaryotic microbiome in the eastern tropical indian ocean - Jinfeng Wang; Wenbin Zhao; Shaodong Zhu; Keyi Huang; Yulin Zhang; Haojin Cheng; Qin Ma; Derui Song; Jiwen Liu; Xiao-Hua Zhang; Xiaolei Wang (Marine Environmental Research, 2026)

Pennsylvanian fusulinids from the Narao section, southern Guizhou, South China and their biostratigraphic significance for the Bashkirian-Moscovian and Moscovian-Kasimovian boundaries - Xinyi Ma; Keyi Hu; Yukun Shi; Xiangdong Wang (Journal of Asian Earth Sciences, 2026)

Crosstalk-free dual-mode electronic skin enabled by selective electrospinning and machine learning-based decoupling - Chu Qin; Qingyin Sun; Chuheng Fu; Keyi Shan; Yuxin Sun; Min Wang (Chemical Engineering Journal, 2026)

Constitutive overexpression of ATP-binding cassette transporters contributes to emamectin benzoate resistance in Spodoptera frugiperda - Congsai Wang; Zikun Wang; Jingdong Li; Yunkun Zi; Huiling Huang; Binrui Bai; Keyi Chen; Jing Wang; Hongsong Chen; Huihua Tan; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Molecular-weight-dependent effects of humic acid on hexavalent chromium accumulation and reduction in green microalgae - Li Luo; Keyi Zhou; Mawuli Dzakpasu; Kena Zhang; Tong Yang; Wenshan Guo; Huu Hao Ngo; Xiaochang C. Wang (Journal of Hazardous Materials, 2026)

Reinforcing the high-rate cycling stability of LiNi0.9Mn0.1O2 cathode by a component-induced structure-microstructure regulation strategy - Keyi Xian; Huanming Zhuo; Xuelong Rao; Yuehuan Peng; Xiangrui Xu; Yanfei Wang; Dong Wang; Chunhui Wang; Xing Ou (Chemical Engineering Journal, 2026)

A plasticity-aware machine learning framework for genomic prediction and resource-efficient wheat breeding under multi-environment conditions - Lei Li; Cong Zhao; Huihui Li; Xi Tian; Jindong Liu; Duoxia Wang; Keyi Wang; Shuaipeng Fei; Guoliang Wan; Jianqi Zeng; Yachao Dong; Jixin Li; et al. (Computers and Electronics in Agriculture, 2026)

Generation of environmentally persistent free radicals in paddy soil and their impact on arsenic speciation and bioavailability: A review - Chen Chen; Nan Yang; Xiaotong Liu; Yi Zhou; Keyi Wang; Naiyi Yin; Xiaolin Cai; Yanshan Cui (Journal of Hazardous Materials, 2026)

Enhanced Chaetoceros muelleri growth using optimized fermented agricultural waste - Yong Feng; Keyi Li; Yutong Xia; Ping Wu; Zhen Wang; Shuhao Huo; Guoqiang Guan; Huayou Chen (Systems Microbiology and Biomanufacturing, 2026)

Multi-isotope coupling models for revealing sulfate source and migration associated with lacustrine groundwater discharge in a large mining area on the Loess Plateau - Zhengguang Zhang; Shen Qu; Xiangyang Liang; Zilong Liao; Yuanzhen Zhao; Keyi Zhang; Chenyu Wang; Fei Gao; Quandong Lian; Ruihong Yu (Process Safety and Environmental Protection, 2026)

β-Ionone inhibits A. sydowii mediated LUAD progression by inhibiting myeloid-derived suppressor cell (MDSC) expansion and activation - Xiaoping Liu; Shuhua Li; Keyi Chen; Xue Yang; Yanxia Yang; Xin Wang (Journal of Molecular Histology, 2026)

Investigation of SNPs at NKCC Gene of Scylla paramamosain to Unveil the Low-Salinity Tolerance Phenotype - Chunyan Yin; Yanqing Ma; Zhiqiang Liu; Xueyang Wang; Keyi Ma; Wei Wang; Chunyan Ma; Fengying Zhang (Fishes, 2026)
The Na+/K+/2Cl− cotransporter (NKCC) gene encodes a critical membrane transporter involved in cellular ion homeostasis and plays a pivotal role in osmoregulation and salinity adaptation in aquatic organisms. This study identified and validated SNP markers in the NKCC gene associated with low-salinity tolerance in Scylla paramamosain. Four SNPs (g.196C>A, g.8374T>A, g.8385T>A and g.91143T>A) were screened and genotyped in low-salinity tolerant and intolerant groups. Association analysis revealed that mutant genotypes at all four sites were significantly enriched in the tolerant group (p

Pollutant control and material conversion of the waste graphite recovered from spent lithium-ion batteries: Preparation of building composite materials - Yusen Wu; Pengcheng Wang; Keyi Lin; Jiaqi Hu; Yonggao Fu; Jie Zhu; Jujun Ruan (Resources, Conservation and Recycling, 2026)

Contrastive mechanisms of lacustrine groundwater discharge and associated pollutant fluxes into two typical inland lakes in Inner Mongolia, Northwest China - Yuanzhen Zhao; Xiaohui Ren; Shen Qu; Fu Liao; Keyi Zhang; Muhan Li; Juliang Wang; Ruihong Yu (Journal of Environmental Sciences, 2026)

Rapid nucleation and wall-climbing growth of methane hydrate by expanded graphite laminates under static high water-loading conditions - Huizhen Yu; Zixuan Song; Keyi Zhong; Daoyi Chen; Yuanyin Wang; Zihan Yue; Jun Duan; Shuyi Jiang; Mucong Zi (Chemical Engineering Journal, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Enhanced buoy-based water quality time series imputation in coastal waters - Minyu Wang; Keyi Yang; Junyu He; Jin Qi; Yijun Chen; Haoqi Gu; Renyi Liu; Sensen Wu; Zhenhong Du (Journal of Hydrology, 2025)

Microbial community assembly and functional adaptation of urease-producing bacteria in oil reservoirs: Driven by phase heterogeneity and selective enrichment - Yanlong He; Keyi Liu; Tengda Huang; Weibo Wang; Xiaoqi Zhang; Lu Bai; Junxi Zhang; Hai Huang (Journal of Environmental Chemical Engineering, 2025)

Initiation of quasi-biweekly oscillation over the equatorial western pacific during El Niño and La Niña developing summers - Kuiping Li; Keyi Wang (Dynamics of Atmospheres and Oceans, 2025)

A high-performance aqueous redox flow battery with long cyclic stability enabled by a novel Janus membrane self-assembled from polyelectrolytes - Quanhu Sun; Keyi Dong; Zefeng Yan; Tian Lv; Yan Tan; Jiaxin Yang; Yu Wang; Weiyang Tang; Tao Chen (Chemical Engineering Journal, 2025)

From heterogeneity to prognosis: understanding the complexity of tertiary lymphoid structures in tumors - Yingying Wang; Dongyan Zhang; Xueping Huang; Guohao Wu; Chuanbao Wang; Jun Li; Song Wang; Xinmiao Xian; Bo Fu; Keyi Li (Molecular Biology Reports, 2025)

Reconfiguration planning and structure parameter design of a reconfigurable cable-driven lower limb rehabilitation robot - Jinghang Li; Keyi Wang; Yanzhuo Wang; Yi Yuan (Medical & Biological Engineering & Computing, 2025)

Multi‐Objective Optimization Design of Irrigation Pipe Networks Based on a Hybrid Harmony Search Algorithm - Qianxi Li; Wuquan He; Wene Wang; Yubao Wang; Zhigong Peng; Chunliang Cui; Keyi Zhao (Irrigation and Drainage, 2025)
This study presents a multi‐objective optimization method for the design of irrigation pipe networks based on a hybrid harmony search algorithm (HEV‐HS). The primary motivations for this study are the challenges of uneven flow, water pressure distribution and frequent pipe failures commonly encountered in large‐scale irrigation pipe network systems. The proposed method minimizes the investment cost of the pipe network and the variance of the surplus head at nodes. A generalized multi‐objective optimization model was formulated to enhance the economic efficiency and operational reliability of irrigation networks. The proposed HEV‐HS algorithm combines harmony search with energy valley optimization and incorporates dynamic adaptive step‐size adjustment alongside an iterative control factor mechanism to increase the ability of the algorithm to escape local optima and improve the quality of the solution set. Simulation tests demonstrated the effectiveness of the proposed method in solving high‐dimensional, complex optimization problems, achieving superior convergence speed and solution quality. An application involving a drip irrigation project in Xinjiang, China shows that the optimized scheme reduces investment costs by 5.1% and decreases the variance of the node surplus hydraulic head by 7.5%. These results confirm the validity and practicality of the method and its potential to improve pressure uniformity and cost efficiency in irrigation pipe network design.

Insights into the combined effect of ofloxacin and humic substances on sewage sludge anaerobic digestion - Sha Long; Zhixiang Hao; Luyang Sun; Dejiang Ren; Keyi Wang; Huiming Li; Dongbo Wang (Environmental Research, 2025)

Selective enrichment of comammox over NOB Nitrospira on biofilm in low-oxygen integrated fixed-film activated sludge system - Yunlong Li; Jin Chen; Bowen Wang; Naif Abdullah Al-Dhabi; Zimin Chai; Keyi Zhang; Shujun Huang; Wangwang Tang; Maosheng Zheng (Journal of Environmental Chemical Engineering, 2025)

Environmental exposure to heavy metals and their potential impact on prostate cancer prognosis-related gene expression - Wei Song; Tao Zhang; Jianliang Ou; Jinliang Ni; Jiong Tang; Houliang Zhang; Haipeng Zhang; Guangchun Wang; Jun Chang; Bo Peng; Keyi Wang (Food and Chemical Toxicology, 2025)

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

MicroalgaeNet: Enhancing recognition of long-tailed marine microalgae images through multi-expert networks and feature compression - Keyi Chen; Sijing Cui; Jiajun Zhong; Qiwei Wang (Algal Research, 2025)

Experimental study on flame characteristics over diesel pool fires under the longitudinal ventilation in curved and inclined tunnels - Xue Wang; Li Yu; Mingnian Wang; Junqi Li; Yuan Liu; Keyi Liu; Zan You (Tunnelling and Underground Space Technology, 2025)

Microbial distribution patterns and driving factors related to nitrogen cycling in karst Tiankeng soil - Xiaohui WANG; Junbo YANG; Keyi WANG; Danjuan ZENG; Ling MO; Gaozhong PU (Pedosphere, 2025)

Synergistic effects of nanoplastics and graphene oxides on microbe-driven litter decomposition in streams - Yao Wang; Keyi Wang; Junbo Yang; Mingquan Dai; Danjuan Zeng; Xiaohui Wang; Jingjing Du; Gaozhong Pu (Journal of Hazardous Materials, 2025)

Impacts of biodegradable microplastics on rhizosphere bacterial communities of Arabidopsis thaliana: Insights into root hair-dependent colonization - Keyi Chen; Zhihui Jin; Qing Zhu; Xiaodie Hu; Sijia Tian; Yulin Wang; Yaru Sun; Ming Yuan; Huaiying Yao (Environmental Research, 2025)

The Middle–Late Pennsylvanian event: Timing and mechanisms - Yixin Wang; Keyi Hu; Xunyan Ye; Xiangdong Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Methanogenic response of paddy soils exposed to zinc oxide nanoparticles and sulfurized products - Minghao He; Rong Tang; Fengyi Guan; Weijie Peng; Jinrong Lu; Keyi Li; Lihua Zhou; Yujie Wang; Yong Yuan (Journal of Hazardous Materials, 2025)

Nitrogen-cycling microbial diversity and function in tiankengs at different evolutionary stages - Xiaohui Wang; Keyi Wang; Junbo Yang; Danjuan Zeng; Ling Mo; Gaozhong Pu (CATENA, 2025)

Application of a fluorescent probe exhibiting a large stokes shift after the precise detection of hydrazine in plants, foods and living cells - Yan Zhang; Yan Huang; Guiyi Yang; Haotian Xin; Keyi Li; Lei Wang; Shangcong Gu; Baosheng Ren; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Synergizing farmland reverting and energy substitution programs in Wolong through agent-based modelling and cost-efficiency analysis - Keyi Liu; Yufeng Chen; Liyan Xu; Xiao Zhang; Zilin Wang; Hailong Li; Yansheng Yang; Hong You; Dihua Li (Ecological Modelling, 2025)

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

Geochemical behaviors of metal elements during a single flood event in the natural Chishui River, Southwest China - Zhongxuan Liang; Keyi Wang; Hongming Cai; Zhongwei Wang; Wei Yuan; Jiubin Chen (Acta Geochimica, 2025)

Temporal and spatial evolution of Mississippian conodonts: A case study - Wenqi Wang; Keyi Hu; Xiangdong Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Structural characteization and anti-colorectal cancer activity of a fucogalactan purified from Ganoderma tsugae - Xin Zhang; Shuai Liu; Keyi Wu; Lili Shu; Yu Li; Lanzhou Li; Di Wang (Carbohydrate Polymers, 2025)

Microscopic influence mechanisms of pre-adsorbed polysaccharide on the nucleation and growth of methane hydrate on metal surface - Ruihua Luo; Keyi Zhong; Daoyi Chen; Guozhong Wu; Li Wang; Mucong Zi (Fuel, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Chronosequence changes in soil microbes under Populus simonii × P. nigra stands: Implications for soil health restoration in Mollisols - Jia Yang; Qinghua Liu; Keyi Liu; Shunzhong Wang; Huiyan Gu (Applied Soil Ecology, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Gonadal expression profiles reveal the underlying mechanisms of temperature effects on sex determination in the large-scale loach (Paramisgurnus dabryanus) - Lei Zhang; Yutong Fang; Mijuan Shi; Keyi Ren; Xin Guan; Waqar Younas; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Animal Reproduction Science, 2025)

Enterovibrio qingdaonensis sp. nov. and Enterovibrio gelatinilyticus sp. nov., two marine bacteria isolated from surface seawater of Qingdao offshore - Keyi Huang; Yi Liu; Yan Wang; Pingping Zhang; Haojin Cheng; Jinfeng Wang; Wanjia Tong; Wang Xiaolei; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2025)

Early estimation of glutelin to gliadin ratio in wheat grain using high-dimensional and hyperspectral reflectance - Junjie Ma; Keyi Wang; Bangyou Zheng; Yinlong Xu; Yong He (Computers and Electronics in Agriculture, 2024)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Decoding PTEN: from biological functions to signaling pathways in tumors - Xueping Huang; Dongyan Zhang; Di Zhang; Jianran Guo; Guohao Gu; Yingying Wang; Guohao Wu; Chuanbao Wang; Bo Fu; Keyi Li (Molecular Biology Reports, 2024)

Identification and characterization of autoallododecaploid barnyard grass (Echinochloa crus-galli L.) induced by in vitro colchicine treatment - Keyi Liu; Xiaoling Zhou; Wei Wang; Xiaoxiao Wu; Ziwei Zhao; Xiaolu Yang; Ziyi Feng; Pincang Lv; Jie Wang; Wangwen Zhu; Xianhua Zhang; Yuchi He; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Immobilization of Pb2+ and Cd2+ in water by sodium alginate magnet-biochar composite and LCA evaluation - Weiwen Dai; Kexin Lu; Juan Zhang; Shulian Wang; Keyi Liu; Huiqin Zhang (Journal of Water Process Engineering, 2024)

An infrared radiation-responsive high-entropy CoCaMgMnAlFe-LDHs for controllable hydrogen generation via NaBH4 hydrolysis: Utilization of steel slag and lithium-ion battery liquid waste - Qiaoqi Li; Fei Wang; Xiaoyan Liu; Wenhao Xu; Keyi Zhang; Siyuan Zhang; Pengfei Teng; Lili Zhang (Chemical Engineering Journal, 2024)

Metal plate-based promotion on methane hydrate nucleation: Insights into the influence of metal type and surface properties - Yuanyin Wang; Mucong Zi; Shuyi Jiang; Keyi Zhong; Daoyi Chen (Chemical Engineering Journal, 2024)

Regulating the generation of singlet oxygen (1O2) in Advanced oxidation processes by catalyst design for water treatment - Yilan Jiang; Keyi Gao; Tingyue Chen; Yiran Xiong; Yingying Li; Abrham Addisu; Suresh C. Pillai; Dionysios D. Dionysiou; Dawei Wang (Chemical Engineering Journal, 2024)

Realizing reasonable redistribution of platform capacity through valence structure optimization for low strain Na3MnZr(PO4)3 cathode material - Mengting Deng; Yulei Sui; Kexin Rao; Yian Wang; Wenbin Fei; Keyi Sun; Zonglin Yang; Xiaoping Zhang; Ling Wu (Chemical Engineering Journal, 2024)

Water–Energy–Land Reallocation and Multiobjective Optimization in the Agricultural System - Jue Wang; Keyi Ju; Xiaozhuo Wei (Water Resources Management, 2024)

Multi-isotopes (δD, δ18Owater, 87Sr/86Sr, δ34S and δ18Osulfate) as indicators for groundwater salinization genesis and evolution of a large agricultural drainage lake basin in Inner Mongolia, Northwest China - Shen Qu; Yuanzhen Zhao; Keyi Zhang; Juliang Wang; Muhan Li; Xu Yang; Xiaohui Ren; Yanling Hao; Ruihong Yu (Science of The Total Environment, 2024)

Separation cathode materials from current collectors of spent lithium-ion battery through low-energy mechanical friction technology - Keyi Lin; Yusen Wu; Ying Shen; Yanrui Zheng; Zicheng Wang; Jinjuan Chen; Taoli Wu; Jie Zhu; Zhe Huang; Baojia Qin; Jujun Ruan (Resources, Conservation and Recycling, 2024)

A novel bimetallic-polyanion Na4Fe2.82Ni0.18(PO4)2P2O7 cathode with superior rate performance and long cycle-life for sodium-ion batteries - Wenbin Fei; Yian Wang; Xiaoping Zhang; Jiuxiang Zhang; Shengxing Lu; Kexin Rao; Keyi Sun; Mengting Deng; Yuxuan Liu; Qingqiang Li; Ling Wu; Yulei Sui (Chemical Engineering Journal, 2024)

Research on energy storage capacity optimization of rural household photovoltaic system considering energy storage sharing - Weijun Wang; Keyi Kang (Environmental Science and Pollution Research, 2024)

Carboniferous integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Keyi Hu; Xiangdong Wang; Wenqi Wang; Yingfan Song; Xunyan Ye; Lu Li; Yukun Shi; Sunrong Yang; Ying Li (Science China Earth Sciences, 2024)

Core-shell nanoconfinement: Nanoreactors for directional electron migration in photothermal-assisted photocatalytic hydrogen production - Yu Shen; Yuxing Shi; Zhouze Chen; Shunhong Zhang; Keyi Chen; Xuefeng Luo; Feng Guo; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2024)

Degradation mechanism analysis of substrate and microporous layer of gas diffusion layer in proton exchange membrane fuel cell - Keyi Xu; Qian Di; Fengman Sun; Ming Chen; Haijaing Wang (Fuel, 2024)

Combining microbiome and pseudotargeted metabolomics revealed the alleviative mechanism of Cupriavidus sp. WS2 on the cadmium toxicity in Vicia unijuga A.Br. - Xuefeng Yuan; Dandan Wu; Dingguo Zhang; Chunyu He; Zilong Wang; Wenqian Xu; Na Shou; Keyi Fu; Mingyuan Yue; Xin Zhang; Zunji Shi (Environmental Pollution, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

Environment relevant exposure of perfluorooctanoic acid accelerates the growth of hepatocellular carcinoma cells through mammalian target of rapamycin (mTOR) signal pathway - Jiawei Hong; Xiaoyan Wang; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Keyi Du; Diyu Chen; Shusen Zheng; Linping Cao (Environmental Pollution, 2024)

The flexible linker and CotG were more effective for the spore surface display of keratinase KERQ7 - Zhen Wang; Mingchen Yan; Muhammad Saeed; Keyi Li; Yanzhen Chen; Charles Obinwanne Okoye; Zhen Fang; Zhong Ni; Huayou Chen (World Journal of Microbiology and Biotechnology, 2024)

Microplastics sequestered in the soil affect the turnover and stability of soil aggregates: A review - Tianhang Ju; Kai Yang; Lei Chang; Keyi Zhang; Xingyi Wang; Jialin Zhang; Bo Xu; Yuefen Li (Science of The Total Environment, 2023)

Large-scale surface water-groundwater origins and connectivity in the Ordos Basin, China: Insight from hydrogen and oxygen isotopes - Shen Qu; Chenyu Wang; Nuan Yang; Limin Duan; Ruihong Yu; Keyi Zhang; Muhan Li; Pengfei Sun (Environmental Research, 2023)

Effects of four diets on the metabolism of megalopa metamorphosis of the mud crab, Scylla paramamosain - Keyi Ma; Zhiqiang Liu; Guangde Qiao; Lingbo Ma; Fengying Zhang; Ming Zhao; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2023)
Dietary intake is an essential source of energy and nutrients, and plays an irreplaceable role in the breeding of S. paramamosain seedlings. In this study, live Artemia nauplii (LA), compound feeds (CF), frozen copepods (FC) and frozen adult Artemia (FA) were utilized as feed during the megalopa stage. To determine the impact that diet has on the metabolism of crablets that underwent metamorphosis from the megalopa stage, analyses of both metabolomics and fatty acid content were conducted. In the LC-MS-based metabolomics analysis, a total of 104, 205 and 83 significantly different metabolites (SDMs) were identified after being fed with FC, FA, and CF, respectively, as compared to the LA group. Furthermore, significant differences in KEGG compounds among the three comparisons exhibited similarity and were mainly associated with categories such as “Lipids”, “Hormones and transmitters”, and “Peptides”. The fatty acid content analysis indicated that the ΣMUFA was significantly higher in the LA and CF groups compared to the other two groups. In contrast, the highest level of ΣPUFA was found in the LA group. In addition, the CF group showed significantly higher expression levels of the fatty acid synthesis genes, FAS and ACC . Conversely, the expression level of the fatty acid decomposition-related gene CPT1 was the highest in the LA group. In comparison with the FA group, the expression level of FABP3 was significantly decreased in the LA and CF groups. In summary, there were significant differences observed in the metabolic profiles of crablets that metamorphosed from the megalopa under different diets. Our experimental results suggested that LA is more advantageous in the cultivation of the S. paramamosain megalopa compared to the other three diets. While it remains a diet that cannot be entirely substituted at present, LA has the potential to improve the culture performance of the S. paramamosain megalopa. The current study could provide valuable data into the development of artificial diets necessary for the future of the mud crab seedling breeding industry.

A comprehensive evaluation of the security of the water-energy-food systems in China - Keyi Ju; Jue Wang; Xiaozhuo Wei; Hao Li; Siyang Xu (Sustainable Production and Consumption, 2023)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Progress in the cultivation of diatoms using organic carbon sources - Keyi Li; Yutong Xia; Zhen Wang; Ebin Gao; Shuhao Huo; Huayou Chen (Algal Research, 2023)

Motion behavior of non-Newtonian fluid-solid interaction foods - Yuhe Fan; Lixun Zhang; Canxing Zheng; Xingyuan Wang; Keyi Wang; Jinghui Zhu (Journal of Food Engineering, 2023)

Suppression of ETI by PTI priming to balance plant growth and defense through an MPK3/MPK6-WRKYs-PP2Cs module - Dacheng Wang; Lirong Wei; Ting Liu; Jinbiao Ma; Keyi Huang; Huimin Guo; Yufen Huang; Lei Zhang; Jing Zhao; Kenichi Tsuda; Yiming Wang (Molecular Plant, 2023)

Physical activity can influence the relationship between ethylene oxide and risk of kidney stones: A cross-sectional study from the NHANES 2013–2016 - Hua Jiang; Keyi Wang; Heng Zhang; Bin Yang; Weipu Mao; Ming Chen; Shuigen Zhou (Environmental Science and Pollution Research, 2023)

Pharmacokinetic profile and sub-chronic toxicity of coenzyme Q10 loaded whey protein nanoparticles - Cuina Wang; Ru Zhao; Keyi He; Siyu Zhang; Alyssa H. Kemp; Mingruo Guo (Food Bioscience, 2023)

Correction to: Relationship between exposure to cadmium, lead, and mercury and the occurrence of urinary incontinence in women - Jinliang Ni; Ziye Li; Yi Lu; Houliang Zhang; Guangchun Wang; Jinbo Xie; Jun Xie; Yidi Wang; Yifan Zhang; Keyi Wang; Weipu Mao; Bo Peng (Environmental Science and Pollution Research, 2023)

Enabling efficiency-driven and low-impact water management from robust decision making: A risk- and robustness-based multi-objective decision support model - Yang Zhou; Bing Li; Jingcheng Han; Guojian He; Keyi Wang; Chunjiang An; Yuefei Huang (Journal of Cleaner Production, 2023)

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

A synthesis of Carboniferous stratigraphy in Xinjiang, Northwest China with emphasis on regional and global correlations - Yong Tang; Xunyan Ye; Xiatian Wang; Xing Huang; Zhangshuai Hou; Keyi Hu; Sunrong Yang; Ying Li; Feifei Zhang; Shuzhong Shen; Xiangdong Wang (Journal of Asian Earth Sciences, 2023)

Potential of granular complexes of lime and montmorillonite for stabilizing soil cadmium and the underlying mechanisms - Gaoxiang Huang; Keyi Huang; Xingxiang Wang; Wuxing Shu; Wenjing Ren; Peng Wang; Hua Zhang; Minghua Nie; Mingjun Ding (Environmental Pollution, 2023)

Response of bacterial communities to shrub encroachment and forage planting in alpine grassland of the Qinghai-Tibetan Plateau - Wenming Ma; Keyi Ding; Song Bai; Changting Wang; Tenzing Droma (Ecological Engineering, 2023)

Relationship between exposure to cadmium, lead, and mercury and the occurrence of urinary incontinence in women - Jinliang Ni; Ziye Li; Yi Lu; Houliang Zhang; Guangchun Wang; Jinbo Xie; Jun Xie; Yidi Wang; Yifan Zhang; Keyi Wang; Weipu Mao; Bo Peng (Environmental Science and Pollution Research, 2022)

RNA-seq Provides Novel Insights into Response to Acute Salinity Stress in Oriental River Prawn Macrobrachium nipponense - Yaoran Fan; Jianbin Feng; Nan Xie; Feiyue Ling; Zefei Wang; Keyi Ma; Xueming Hua; Jiale Li (Marine Biotechnology, 2022)

Simultaneous determination of the four key fluoroquinolones and two antipsychotics in fish and shrimp by LC-MS/MS - Keyi Shen; Xiaoshuang Zou; Jun Wang (Food Additives & Contaminants: Part A, 2022)

Effect of Dissipation on the Moonpool-Javelin Wave Energy Converter - Dan Yu; Keyi Wang; Yeqing Jin; Fankai Kong; Hailong Chen; Can Yang (Journal of Marine Science and Engineering, 2021)
In this work, the hydrodynamic performance of a novel wave energy converter (WEC) configuration which combines a moonpool platform and a javelin floating buoy, called the moonpool–javelin wave energy converter (MJWEC), was studied by semianalytical, computational fluid dynamics (CFD), and experimental methods. The viscous term is added to the potential flow solver to obtain the hydrodynamic coefficients. The wave force, the added mass, the radiation damping, the wave capture, and the energy efficiency of the configuration were assessed, in the frequency and time domains, by a semianalytical method. The CFD method results and the semianalytical results were compared for the time domain by introducing nonlinear power take-off (PTO) damping; additionally, the viscous dissipation coefficients under potential flow could be confirmed. Finally, a 1:10 scale model was physically tested to validate the numerical model and further prove the feasibility of the proposed system.

Advances in Research on the Toxicological Effects of Selenium - Qizhuang Lv; Xiaomei Liang; Keyi Nong; Zifeng Gong; Ting Qin; Xinyun Qin; Daobo Wang; Yulin Zhu (Bulletin of Environmental Contamination and Toxicology, 2021)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Host Response to Pulmonary Fungal Infections: a Highlight on Cell-Driven Immunity to Cryptococcus Species and Aspergillus fumigatus - Orchi Dutta; Jorge A. Masso-Silva; Keyi Wang; Amariliz Rivera (Current Pharmacology Reports, 2017)

Dihydromyricetin Ameliorates 3NP-induced Behavioral Deficits and Striatal Injury in Rats - Shuhua Mu; Youlan Li; Bingbing Liu; Weiping Wang; Si Chen; Jiajia Wu; Lisi OuYang; Yaxi Zhu; Keyi Li; Mali Zhan; Zongwei Liu; Yu Jia; et al. (Journal of Molecular Neuroscience, 2016)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

Bio-resolution of glycidyl (o, m, p)-methylphenyl ethers by Bacillus megaterium - Zhengfang Zhang; Yanming Sheng; Keyi Jiang; Zhao Wang; Yuguo Zheng; Qing Zhu (Biotechnology Letters, 2010)

A novel SNP of the Hesx1 gene in bovine and its associations with average daily gain - Xinsheng Lai; Xianyong Lan; Hong Chen; Xinlei Wang; Keyi Wang; Mou Wang; Hui Yu; Miao Zhao (Molecular Biology Reports, 2009)